Propensity Score to Compare Pars Plana Vitrectomy and Scleral Buckling in Retrospective Studies [Letter] - Visioli G; Alisi L; Albanese GM (Clinical Ophthalmology)
Giacomo Visioli, Ludovico Alisi, Giuseppe Maria Albanese Department of Sense Organs, Sapienza – University of Rome, Viale del Policlinico 155, 00161, RomeCorrespondence: Giacomo Visioli, Department of Sense Organs, Sapienza University of Rome, Viale del Policlinico 155, 00161, Rome, Tel +39 0649975389, Email giacomo.visioli@uniroma1.it